Health status evaluation of type 2 diabetes patients from two hospitals of northern Peru - León-Jiménez, Franco (2021)
Objetive: To describe illness related knowledge features, mental health, adherence to therapy and quality of life on type 2 diabetes patients from two hospitals from northern Peru. Material and Methods: Cross sectional descriptive study. A cense was made. Descriptive statistics and exploratory analysis were employed. Results: there were 382 diabetes patients: 289 in Lambayeque and 93 in Piura:112 people were interviewed. The mean age was 59.5 +/- 11.6 years, 58% were women, 59% were from Piura, 43.8% only had primary school and 41.5% referred 2 to 4 outpatient evaluations in the last two years; 28.6% reported to have been infected by COVID-19: 35,5% in Lambayeque and 23.8% in Piura; 17.8% had poor knowledge about the disease. About mental health, 91.9% had Depression, 75% Anxiety and 72.8%, both; 50.6% had adequate adherence to therapy. The median of quality of life was 161.5 (IQR=127.1-215) and 24.1% had poor quality of life. In descending order, the more affected dimensions of quality of life were: “control of diabetes”, “energy and mobility”, “social burden”, “anxiety” and “sexual performance”. In the exploratory multivariate analysis, depression was associated with high quality of life. Conclusion: disease related-knowledge features, mental health, adherence to therapy and quality of life were poor on type 2 diabetics from these two northern cities of Peru. There were no association between sociodemographic characteristics, mental health, knowledge, adherence, with quality of life.